Pleistocene freshwater environments of Poland: a comprehensive study of fish assemblages based on a multi‐proxy approach. (20th November 2020) - Stefaniak, Krzysztof; Kovalchuk, Oleksandr; Kotusz, Jan; Stachowicz‐Rybka, Renata; Mirosław‐Grabowska, Joanna; Winter, Hanna; Niska, Monika; Sobczyk, Artur; Barkaszi, Zoltán; Kotowski, Adam; Malkiewicz, Małgorzata; Alexandrowicz, Witold Paweł; et al.
Abstract : The results of a comprehensive study of Pleistocene fish‐bearing localities from the territory of Poland are presented. Fish remains came from lacustrine deposits and cave sites representing a time‐span from the late Early Pleistocene until the Early Holocene. Here we present the taxonomic composition and species diversity of all known fish assemblages from Poland. In total, 23 species belonging to 20 genera of eight families were identified. Cyprinids were the most taxonomically diverse, followed by salmonids and percids. Other families were each represented only by a single species. The roach, rudd, bream, pike and perch were the most common components of the Pleistocene fish assemblages of Poland. These assemblages are clearly divided into two groups representing palaeolakes and cave sites. A significant taxonomic similarity is observed between fish assemblages from Poland and those of Chibanian and Late Pleistocene ages from central and eastern Europe. Pleistocene environments and climates of Poland are characterized using a multi‐proxy approach (analysis of stable isotopes, plant macro‐remains, pollen, molluscs and cladocerans). Obtained data allowed us to estimate a number of parameters of Pleistocene water bodies of the Polish Lowland (reservoir type, trophism, oxygen content, depth and water level changes, bottom character, and flow speed). The formation of freshwater fish assemblages was influenced by dynamic changes in the hydrographic network, and climatic changes during the Pleistocene and Holocene. Their development was favoured by the formation of lakes after melting of the ice sheet.